2007
DOI: 10.1063/1.2721077
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of high energy excited deuterium atoms in a hollow cathode glow discharge

Abstract: The presented results are concerned with the shape of the Balmer alpha line emitted from a low pressure dc glow discharge with stainless steel (SS) and titanium (Ti) hollow cathode (HC) with D2 or Ar∕D2∕H2 gas mixture. The analysis indicates that the line profile represents a convolution of three Gaussian profiles resulting from different collision excitation processes. The average energy of excited deuterium atoms determined from the width of the broadest Gaussian is about 86eV in both HCs. In Ar∕D2∕H2 gas mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Several experiments including the recent ones showed that the profiles observed perpendicular to the discharge axis ͑side-on͒ as symmetric [1][2][3][8][9][10][11][12][13][14] where as the profiles obtained at the end of the discharge axis ͑end-on͒ as asymmetric with enhanced blue wings. [1][2][3][4][5][6][7] Whether, end-on or side-on, in both the cases, the EB was detected.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several experiments including the recent ones showed that the profiles observed perpendicular to the discharge axis ͑side-on͒ as symmetric [1][2][3][8][9][10][11][12][13][14] where as the profiles obtained at the end of the discharge axis ͑end-on͒ as asymmetric with enhanced blue wings. [1][2][3][4][5][6][7] Whether, end-on or side-on, in both the cases, the EB was detected.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Study of these discharges has many important applications in the field of plasma surface interactions, low temperature electrical discharges used for plasma processing, and fusion plasmas. Despite of many detailed studies reported on these discharges, complete understanding on various fundamental processes governing in plasma-wall transition ͑sheath͒ region is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[33] and references therein. The same types of reactions ( 1)-( 3) are expected in deuterium and, consequently, similar interactions with cathode surface occur [1].…”
Section: Introductionmentioning
confidence: 55%
“…There is considerable interest in the shape of Balmer lines emitted from a low-pressure discharge operating with hydrogen isotopes and with hydrogen-inert gas mixtures, see e.g. [1]. The interest is triggered primarily by large excessive Doppler broadening (EDB) of hydrogen Balmer lines detected first time from hydrogen and hydrogen-inert gas mixtures in a hollow cathode (HC) glow discharge (GD) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation